2016
DOI: 10.35864/evmd.514501
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Virulence Factors among Fish Originated Enterococci

Abstract: Enterococci are commensal organisms of human and animals, and may cause diseases in particular conditions. Several virulence factors are responsible in the production of diseases. The aim of this study was to isolate enterococci from fish and to determine virulence factors of the isolates. A total of 26 (13%) Enterococcus faecalis strains were isolated from live, moribund and dead fish collected from fish farms in Aegian Region. Cytolysin and gelatinase activities and aggregation substance production of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
(48 reference statements)
0
3
0
2
Order By: Relevance
“…Savaşan et al. (2016) stated that AS and gelE virulence factors were detected in 26.9% and 11.5% of E. faecalis isolates of fish samples in Turkey. Araújo et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Savaşan et al. (2016) stated that AS and gelE virulence factors were detected in 26.9% and 11.5% of E. faecalis isolates of fish samples in Turkey. Araújo et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports showed that the high distribution of some virulence factors, particularly efa, ebpA, ebpB, ebpC, and esp in the E. faecalis strains, guaranteed the high pathogenicity and clinical disease occurrence by these strains (Chen et al, 2018;Stępień-Pyśniak et al, 2019). Savaşan et al (2016) detected in some isolates. This gene is responsible for the pathogenicity island, biofilm formation, and dynamics of antibiotic release (Leavis et al, 2004).…”
Section: Surveys Conducted Bymentioning
confidence: 99%
“…In addition to the recorded economic losses caused by bacterial diseases in fish farms, many of these microorganisms are incriminated as causative agents for many human health hazards. With this concern, Enterococcus faecalis , a microorganism that shows pathogenicity and virulence factors among fish (Savaşan et al, 2016), has been isolated from human urine (Colman, 1967). In Egypt, Aerococcus viridans and Enterococci have been isolated from Nile tilapia ( Oreochromis niloticus ) in both aquaculture and wild sites (Osman et al, 2017); E. faecalis was also isolated from poultry manure (Bogaard et al, 2002), cattle manure, and cattle milk (Nobukazu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Τα Lactobacillus spp., έχουν βρεθεί να είναι η κυρίαρχη ομάδα αλλοιωγόνων μικροοργανισμών σε διάφορα καπνιστά αλιεύματα, όπως καπνιστό σολομό και πέστροφα (ψυχρής κάπνισης; Hansen et al, 1995;Hansen & Huss, 1999;Lyhs, 1999) αλλά και σε άλλα επεξεργασμένα αλιευτικά προϊόντα, όπως είναι οι μαριναρισμένες αντσούγιες, σαρδέλες και ρέγκες (Fuselli et al, 1998;Lyhs et al, 2001a;Kilinc & Cakli, 2005;Sallam, 2008). Τα Gram θετικά βακτήρια της οικογένειας των Εντερόκοκκων, απομονώνονται συχνά από τις ιχθυοκαλλιέργειες και αποτελούν μία από τις πιο κοινές αιτίες πρόκλησης ασθενειών στην υδατοκαλλιέργεια παγκοσμίως (Martins et al, 2008;Savaşan et al, 2016). Το E. faecalis, απαντάται συχνότερα στα ψάρια και είναι υπεύθυνο για τον μεγαλύτερο αριθμό των προκαλούμενων ασθενειών (Rahman et al, 2017).…”
Section: προσδιορισμός υγρασίαςunclassified
“…Τα Enterococcus spp. εκτός από τους ζωντανούς οργανισμούς μπορεί συχνά να απομονώνονται από το περιβάλλον αλλά και από διάφορα τρόφιμα (Pinto et al,1999;Harwood et al, 2001;Savaşan et al, 2016). Σε συμφωνία με αυτό, η απομόνωση του E. faecalis, από τα φιλέτα που μελετήσαμε θεωρήθηκε ως περιβαλλοντική επιμόλυνση.…”
Section: προσδιορισμός υγρασίαςunclassified